EFFECT OF PEOPLE IN LIQUID SMOKE ON QUALITY OF MICROBIOLOGY OF LELE FILLETS (Clarias sp) DURINGCOLD STORAGE 5 ° C - Stella Puspaning Mawarni; Syahrul Syahrul; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                     This study is aimed to determine the effect of immersion in liquid smoke on microbiological quality of storage catfish fillets at cold temperatures (5 ° C) and to find out the best concentration of liquid smoke on microbiological quality of catfish fillets during storage at cold temperatures (5 ° C), with concentration treatment liquid smoke was 4% (A1) 6% (A2) and 8% (A3) during storage period of 0, 10, 20 and 30 days. Based on the results of research carried out soaking catfish fillets in liquid smoke with concentrations of 4%, 6%, 8%, it was significantly affected to the total of plate count andthe total of Staphylococcus aureus bacteria. Escherichia coli bacteria and Salmonella sp bacteria were negative and Setra had significant effect on organoleptic values (odor and appearance). Based on the results of the tested parameters, the best treatment was soaking catfish fillets in liquid smoke concentration of 8% with the total plate count value of 1.1x105 cells/gram, the total value of Staphylococcus aureus bacteria was 6.8x102 cells/gram. It was negative for Escherichia coli bacteria. Salmonella sp bacteria were negative with storage period of 30 days. As well as organoleptic testing with the appearance value of 6.52 with characteristics of slightly brownish white meat, less bright, less attractive, odor value 6.60 with specific aroma with distinctive smelling smoke, organoleptic texture with value 6.76 with elastic characteristics with storage periodof 10 days.Keywords: liquid smoke, fillets, catfish, cold storage 5 ° C